Application of Cat Swarm Optimization for Recognition of Handwritten Numerals - Pujari, Puspalata; Majhi, Babita (International Journal of Computer Sciences and Engineering, 2025)
Accurate recognition of optical handwritten numeral is still an open and demanding problem in present digital world. The basic objective of the present work is to develop a novel method for recognition of off line unconstrained handwritten Odia numeral using curvature feature and functional link artificial neural network (FLANN) based cat swarm optimization (CSO) technique. In this paper preprocessing and feature extraction steps are carried out before the recognition of numerals. For feature extraction curvature based approach is applied. For recognition of handwritten Odia numeral hybrid architecture has been proposed where the classification task is performed by FLANN classifier and cat swarm optimization is used for finding a suitable set of weights for the FLANN classifier. The proposed model is evaluated on database consisting of 4000 number of handwritten Odia numerals. The combined effect of curvature based feature extraction approach and FLANN based cat swarm optimization technique yielded a high accuracy which exhibits the effectiveness of CSO based FLANN optimization model (FLANN-CSO) for recognition of Odia handwritten numerals